2023
DOI: 10.3389/ijph.2023.1605606
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Literacy and Vaccination: A Systematic Review

Abstract: Objectives: Vaccine literacy (VL) is an essential component of health literacy and is regarded as the promising technique for eliminating vaccine hesitancy. This review summarizes the relationship between VL and vaccination, including vaccine hesitancy, vaccination attitude, vaccination intention, and vaccination uptake.Methods: A systematic search was conducted in the PubMed, Embase, Web of Science, CINAHL, PsycINFO, and Cochrane Library databases. Studies that explored the relationship between VL and vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 51 publications
4
27
1
Order By: Relevance
“…The recent meta-analysis published by Isonne et al 1 on HV&I confirms the positive role of vaccine literacy (VL) to predict vaccine intention, as already shown by other reviews, 2–4 while its association with vaccination status (vaccine uptake) is less significant. As pointed out by the authors, this could be linked, among others, to some aspects of convenience, including the accessibility and quality of vaccination clinics and the time and availability of people to be vaccinated.…”
supporting
confidence: 53%
“…The recent meta-analysis published by Isonne et al 1 on HV&I confirms the positive role of vaccine literacy (VL) to predict vaccine intention, as already shown by other reviews, 2–4 while its association with vaccination status (vaccine uptake) is less significant. As pointed out by the authors, this could be linked, among others, to some aspects of convenience, including the accessibility and quality of vaccination clinics and the time and availability of people to be vaccinated.…”
supporting
confidence: 53%
“…Currently, there is no concordance in the literature on the role of parent’s educational attainment in their children’s vaccinations [ 26 27 ]. According to recent evidence, factors more specific than parent’s educational attainment, such as health literacy or vaccination literacy, may have a greater impact on children’s vaccination uptake [ 28 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not only in contrast with the scientific facts (scientific studies have shown that the efficacy of Chinese COVID-19 vaccines such as Sinovac and Sinopharm is around 86%, compared to 95% for Pfizer and 94% for Moderna) ( 13 , 14 ), but also with previous published data. For example, based on a meta-analysis of 58 articles about Chinese public attitudes toward various vaccines, Wang et al ( 10 ) found that almost one half of respondents don't trust domestic vaccines' effectiveness, nor their safety, and that they were more willing to take imported vaccines where these were available. Another study, about Chinese parents' and caregivers' attitudes toward foreign and domestic vaccines for children, showed that respondents found the two comparable and as having similar levels of effectiveness and safety ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the findings of previous studies showing that Chinese people trust more or at least equally imported vaccines compared to domestic vaccines for protecting against measles-mumps-rubella, HPV, and other diseases ( 10 , 11 ), what might be their perceptions of COVID-19 vaccines from China and other countries? Compared to the former vaccines, with which people are quite familiar, those for COVID-19 are totally new and have been developed in a very short timeframe.…”
Section: Introductionmentioning
confidence: 99%